Analisis Rasio Profitabilitas dan Likuiditas Dalam Menilai Laporan Keuangan Pada PT. Mayora Indah Tbk Periode 2018-2022 di Bursa Efek Indonesia - Tri Cahyo Nugroho (UNIVERSITAS RAHARJA, 2023)
Financial performance is one of the indicators in assessing a company's success in generating profits. Financial performance in this case is measured through the Profitability Ratio through the measuring tools Net Profit Margin, Return On Equity and Return On Assets, while Liquidity is measured through the Current Ratio and Quick Ratio. This study aims to determine Profitability ratios seen from Net Profit Margin, Return On Assets and Return On Equity and Liquidity ratios seen from Current Ratio and Quick Ratio at PT. Mayora Indah Tbk Period 2018-2022. Analysis of Financial Statements with Profitability and Liquidity ratios in this study is based on Kashmir's opinion. The method used in this research is descriptive quantitative. The results of this study based on profitability ratios indicate that the company's financial performance is poor and inefficient as seen from the average value of the company's Net Profit Margin (NPM), Return On Equity (ROE) and Return On Assets (ROA) ratios below the industry standard average value in the opinion of Kashmir and below the actual standard average time series for the food and beverage industry of a similar kind. Based on the Liquidity ratio, it shows that the company's financial performance is very good and efficient, seen from the average value of the company's Current Rati and Quick Ratio ratios above the industry standard average value in the opinion of Kashmir and above the actual average time series standard for the food and beverage industry of a similar kind.